The wilds of Madagascar (Pittsburg : National Geographic Society, 1988)
Just off the east coast of Africa, Madagascar is an island in all the world. Separated from the mainland 165 millions years ago, Madagascar's flora and fauna have evolved in near isolation. Joint a team of naturalists as they trek to the island's, remote Ankarana plateau to study the exotic animals of this forbidding wildlife oasis
APD 2433